2017
DOI: 10.1002/mrm.26574
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of respiratory motion suppression techniques for 4D flow MRI

Abstract: PurposeThe purpose of this work was to assess the impact of respiratory motion and to compare methods for suppression of respiratory motion artifacts in 4D Flow MRI.MethodsA numerical 3D aorta phantom was designed based on an aorta velocity field obtained by computational fluid mechanics. Motion‐distorted 4D Flow MRI measurements were simulated and several different motion‐suppression techniques were evaluated: Gating with fixed acceptance window size, gating with different window sizes in inner and outer k‐sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 23 publications
3
35
1
Order By: Relevance
“…A small bias towards higher velocities was observed for 5D Flow LLR compared to the 4D Flow reference. This can be related to previous findings that respiratory motion leads to blurring of the image [20, 51] which corresponds to spatial low-pass filtering and is therefore likely to reduce peak velocities.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A small bias towards higher velocities was observed for 5D Flow LLR compared to the 4D Flow reference. This can be related to previous findings that respiratory motion leads to blurring of the image [20, 51] which corresponds to spatial low-pass filtering and is therefore likely to reduce peak velocities.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, data acquisition without respiratory motion compensation leads to decreased image quality [14]. Accordingly, navigator-based respiratory gating is typically employed [20]. Unfortunately, respiratory gating makes scan times unpredictable, as gating efficiencies vary among subjects and often even during a single scan.…”
Section: Introductionmentioning
confidence: 99%
“…Garg et al speculate that the better EPI performance found in their study could be explained by a shorter acquisition time that could have reduced respiratory artifacts in their nonrespiratory motion suppressed sequences. Here, we employed a respiratory navigator, as it drastically decreases errors associated with respiratory motion in 4D Flow MRI . Indeed, the results for SGRE were considerably better in our study, but we find it unlikely that the lack of respiratory motion compression would affect the SGRE and EPI sequence very differently.…”
Section: Discussioncontrasting
confidence: 73%
“…The volunteer and patient studies were used to evaluate respiratory control effects. Furthermore, it would be interesting to compare in vivo in a future work the different existing respiration motion correction methods, as was recently performed using numerical simulations . Finally, technical limitations include the anisotropic voxel size, and long reconstruction times when using the PEAK‐GRAPPA method, which was up to 10 minutes for the SRes1 datasets.…”
Section: Discussionmentioning
confidence: 99%